Gratification development in corruption in Indonesia - arimansitompul, arimansitompul (International Asia Of Law and Money Laundering, 2024)
The background of this article is the number of cases of gratuities received by state administrators / officials that cause corruption bribery. The purpose of this article is to find out the general overview and regulation of gratuities and analysis of gratitude that can be a corruption of gratuities. In this writing, normative legal methods are used, the solution of which is based on literature and legislation. The conclusion in this writing is that gratification can be classified as bribery corruption and a sign of gratitude that can be a gratuitous type of corruption. Acceptance of such gratuities is contrary to its obligations. In order for the gratuity not to be considered a corruption offense of bribery, the recipient must submit a report to the Corruption Eradication Commission, no later than 30 days after receiving the gratuity.